The usage of computer integrated classroom (cic) technology tools in the study of interactions of knowledge construction among esl pre-service teacher - Salam, Abdul Rahim; Tasir, Zaidatun; Abdul Samad, Adlina (2008)
This paper takes a glimpse at the possible tools for collecting data on interactions of knowledge construction among ESL pre-service teacher. The main tool identified to compile the data collection of the study is a customized of computer integrated classroom (CiC) system. For that purpose, a pilot study on computer support face to face peer response using CiC was trialed with a group of students enrolled in a Microteaching course at the Faculty of Education, University Technology Malaysia. CiC was explored to see whether the system could facilitate both modes of synchronous interactions: text-based reporting and verbal interaction. With the assistance of software and hardware integrated in CIC, many computer supported collaborative learning activities could be carried out by ESL pre-service teachers such as recording, storing, retrieving, and monitoring of user profiles’ activities, learning materials and interactions.